Interferon downstream signaling is activated early in pre-symptomatic Niemann-Pick disease type C. (27th July 2019) - Shin, Samuel D.; Shin, Alexandra; Mayagoitia, Karina; Wilson, Christopher G.; Bellinger, Denise L.; Soriano, Salvador
Graphical abstract: Highlights: IFN-γ- and IFN-α-responsive genes are aberrantly upregulated. Microglial activation, anti-viral response, T-lymphocyte activation, and T-lymphocyte chemotaxis pathways are activated. IP-10/CXCL10 is a key neuroinflammatory cytokine in early and terminal disease. Abstract: Niemann-Pick disease type C (NPC) is a fatal neurodegenerative condition with no FDA-approved therapy. Previous studies demonstrated that neuroinflammation is an early pathologic event and a disease modifier of NPC, affecting symptomatic onset and overall lifespan. Therefore, NPC-specific anti-inflammatory therapy may result in clinical benefit. However, to date, the initial trigger of the inflammatory onset and the mechanism driving the sustained chronic neuroinflammation remain unknown. In this study, we utilized a genome-wide transcriptome analysis to identify the key pathways involved in early NPC. Our results showed that an atypical pattern of interferon downstream signaling that involves both IFN-γ- and IFN-α-responsive genes is activated in pre-symptomatic Npc1 −/− cerebella. Functional analysis of the differentially expressed genes highlighted microglial activation, anti-viral response, and T-lymphocyte activation and chemotaxis pathways. Multiplex protein analysis confirmed that a potent IFN-γ-responsive cytokine, IP-10/CXCL10 was significantly upregulated in the pre-symptomatic stage and further exacerbated in the terminal stage. In addition, several IFN-γ-responsive cytokines were elevated in the terminal stage Npc1 −/− cerebella, including MIG/CXCL9, MCP-1/CCL2, MIP-1α/CCL3, MIP-1β/CCL4, RANTES/CCL5, M-CSF, and IL-1α. Together, our results describe a novel activation pattern of interferon downstream signaling in pre-symptomatic NPC, as well as key inflammatory mediators that could serve as potential targets for NPC-specific anti-inflammatory therapy.